Telephone follow-up based on empowerment theory to improve resilience and quality of life among patients after coronary artery stent implantation: a randomized controlled trial - Hua, Yan; Wang, Mei; Li, Lu; Guo, Chunmian; Huang, Zhaoxu; Li, Yang; Lin, Yue; Xiao, Yingjing; Ni, Chunping; Lv, Aili (Frontiers in Psychiatry, 2024)
Background: Coronary heart disease has a high incidence rate, high mortality rate, high recurrence rate and high medical cost. In addition, some patients need to undergo percutaneous coronary stent implantation (CASI), which is a kind of traumatic treatment. Patients can easily experience negative emotions such as anxiety and depression after surgery, which seriously affects quality of life.Objectives: To evaluate the effectiveness of an empowerment-based telephone follow-up intervention on resilience and quality of life in patients who underwent coronary artery stent implantation.Design: Randomized controlled trial.Results: After a one-month telephone follow-up intervention based on the empowerment theory for patients after coronary artery stent implantation, the variation in knowledge related to coronary heart disease and it's all subscales scores were greater in the intervention group than in the control group. Except for the three dimensions of risk factor, induction factor and rehabilitation-related knowledge, the variation in knowledge related to coronary heart disease and the other subscale scores were significantly different between the two groups (P＜0.05). The variations in resilience and scores on the 3 subscales in the intervention group were greater than those in the control group, and the difference between the two groups was statistically significant (P＜0.05). The variation in the quality of life and overall health, emotional functions and social functions were significantly greater in the intervention group than in the control group (P＜0.05).Conclusions: A telephone follow-up intervention based on the empowerment theory can effectively improve the resilience and quality of life of patients after coronary artery stent implantation. This follow-up approach can provide a theoretical basis and practical reference for hospitals and communities to carry out targeted continuing nursing for patients after coronary artery stent implantation. The long-term effects of the intervention and its underlying mechanisms require further study.